Role of irisin in bone diseases - Zhao, Ruobing; Chen, Yan; Wang, Dongxue; Zhang, Chunyu; Song, Henan; Ni, Guoxin (Frontiers in Endocrinology, 2023)
Bone diseases are common among middle-aged and elderly people, and harm to activities of daily living (ADL) and quality of life (QOL) for patients. It is crucial to search for key regulatory factors associated with the development of bone diseases and explore potential therapeutic targets for bone diseases. Irisin is a novel myokine that has been discovered in recent years. Accumulating evidence indicates that irisin has beneficial effects in the treatment of various diseases such as metabolic, cardiovascular and neurological disorders, especially bone-related diseases. Recent studies had shown that irisin plays the role in various bone diseases such as osteoarthritis, osteoporosis and other bone diseases, suggesting that irisin may be a potential molecule for the prevention and treatment of bone diseases. Therefore, in this review, by consulting the related domestic and international literature of irisin and bone diseases, we summarized the specific regulatory mechanisms of irisin in various bone diseases, and provided a systematic theoretical basis for its application in the diagnosis and treatment of the bone diseases.